Identification and estimation of the intake of fermented foods and their contribution to energy and nutrients among Japanese adults - Hitomi Fujihashi; Satoshi Sasaki (Cambridge University Press, 2024)
Abstract Objective: Few studies have reported intakes of fermented foods with their clear definitions. This study aimed to identify fermented foods and beverages consumed in Japan based on international definitions and to estimate their intake and contribution to energy and nutrients. Design: Data from a 16-d (four non-consecutive days within each season at 3-month intervals) semi-weighted dietary records (DR) were used. To identify 'entirely fermented foods' and 'partially fermented foods', a literature search on food processing and ingredients was conducted for all foods that appeared in the DR. For 'partially fermented foods', only the weight of the fermented food component was included in the estimation of total fermented food intake. Setting: Four regions in Japan: Osaka, Nagano, Tottori and Okinawa. Participants: Two-hundred forty-two apparently healthy Japanese adults aged 31-81 years. Results: Of the 1396 kinds of unique foods that appeared in the DR, 101 were 'entirely fermented foods' and 104 were 'partially fermented foods'. The mean intake of fermented foods was 438 g/d per person (17 % of the total weight). They were mainly derived from beer, coffee, bread and yogurt. The mean contribution of fermented foods to the total energy intake was 18 %. For nutrients, the contribution to total intake was high to Na (46 %), Mg (22 %) and Ca (20 %). Conclusions: Fermented foods account for approximately one-fifth of the total weight and energy of dietary intake and are important contributors to some nutrients in Japanese adults.